SYSTEMATIC ANALYSIS OF RESEARCH TRENDS OF AL-QIRA'AH MATERIAL IN SENIOR HIGH SCHOOL ARABIC TEXTBOOKS - Ubaidillah, Moch; Yusril Ihza Elyas; Husnul Hamidah; Slamet Daroini (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study aims to analyze scientific research trends related to al-Qirā’ah material in Arabic textbooks for senior high school (SMA/MA) in Indonesia. Employing a Systematic Literature Review (SLR) approach, eight academic articles published between 2020 and 2025 were thematically and conceptually examined. The review focuses on the alignment of reading materials with the national curriculum's Basic Competencies (KD), the integration of spiritual and social values, the linguistic structure and sequencing of texts, and the contextual relevance to the developmental characteristics of 17–18-year-old students. The findings reveal that most al-Qirā’ah materials have not fully addressed curriculum demands, particularly in promoting higher-order thinking skills, character reflection, and contextual engagement. The study concludes that Arabic reading materials should be designed to be not only curriculum-aligned but also contextual, progressive, and integrative. These findings are expected to inform textbook developers and educational policymakers in enhancing the quality of Arabic language instruction.